The Influence of English-Speaking Anxiety on Learning Attitude of Chinese Non-English Major Undergraduates : Motivation as a Mediator. - Wenxin, Lu; Joseph, Ramanair (Asian Journal of Arts, Humanities and Social Studies, 2025)
This study explores how English-speaking anxiety affects non-English major students' learning attitudes in China, highlighting motivation's mediating role. In China's higher education, English learning, especially oral skills, is crucial. However, English learning anxiety impacts students' attitudes towards spoken English. Employing standard measures and literature, multiple regression shows oral anxiety significantly shapes learning attitudes, with motivation as a key mediator. Despite the acknowledged importance of English oral proficiency in higher education, a substantial number of non-English major students in China continue to experience considerable levels of speaking anxiety. This anxiety adversely affects their willingness to engage in classroom oral activities and poses significant challenges to the cultivation of positive learning attitudes. Notably, the role of underlying motivational mechanisms in this context has received limited empirical attention within Chinese university settings. To address this gap, the present study employed a quantitative research approach using a survey design to collect data from undergraduate students. The final sample comprised 198 participants, including 49.49% male (n = 98) and 51.51% female (n = 100), all enrolled in non-English major programs at Chinese universities. The study discusses findings, gives anxiety-management suggestions, and notes limitations. It concludes that Chinese universities should consider students' attitudes to boost learning efficiency. Future research could examine more influencing factors, expand samples, conduct qualitative studies on different age groups, and use longitudinal methods.